PENGARUH MOTIVASI, PERSEPSI DAN PENGETAHUAN PAJAK TERHADAP MINAT MAHASISWA DALAM PEMILIHAN KARIR DI BIDANG PERPAJAKAN - manurung, henok rolencius; Efriyenti, Dian (SCIENTIA JOURNAL, 2024)
This research aims to analyze the factors of accounting program (study) students in choosing their job or profession after graduating from the Faculty of Accounting, and also this research analyzes the general differences between students in the accounting study program who have studied taxation. The factors analyzed in this research are motivation factors, perceptions and knowledge of taxation at five universities on Batam Island, both state universities and private universities that have accounting study programs. The scope of students who were respondents were Accounting study program students who had studied taxation in the 5th semester and students in the 6th semester. The population in this study was 1,094 purposive respondents and 293 Convenience students. The results of this research show that students on Batam Island who work while studying only focus on careers in student work, influence, motivation and interest in the field of taxation. In this research, students only focus on career work with support in the field of Accounting because students on Batam Island work while studying. .Keywords: Interest In Career Selection In Taxation; Motivasion, Perception; Tax Knowladge